The participation of the fishing communities in the development of Iloilo River - Dela Cruz, Rudolph Elmo F (Miagao, Iloilo University of the Philippines Visayas, 2008)
A study to determine the participation of the fisherfolk community of Station 4 living along the Iloilo River in relation to the implementation of the Iloilo River Development Master Plan was conducted. The study also looked at the extent of implementation of the master Plan. As part of the management scheme, the extent of the River was divided into 4 Stations. Results show that the Iloilo River is still experiencing increasing anthropogenic pressure, not only from residential areas located along the River but also from business establishments, restaurants, eateries and a hospital also situated near the River. The Iloilo River development Master Plan is still not fully implemented in spite of its adoption by the City Government in 2003. Only Station 1 has its Implementing Rules and Regulation, which was only approved in 2007. Thus, there is no single agency to direct and coordinates all conservation and protection efforts for the River. Different government agencies simply perform their own respective mandates. As a results of this, the residents and fishers of Station 4, led by their Barangay Fisheries and Aquatic Resources Management Council and Barangay Council, conduct their own cleanliness drive and river clean-up activities. The fishers and the residents are willing to protect the river and actively participate in the implementation of the Iloilo River Development Master Plan. However, there are still problems associated with the River Management. These include increasing settlement of informal settlers, indiscriminate disposal of garbage and waste products and overcrowding of stationary fishing gears in the river.
Special Problem (MMA) -- Miagao, Iloilo : U.P. Visayas, 2008.
Keywords: Fishing communities -- Iloilo River